LBS URUN DANA: PLATFORM EQUITY CROWDFUNDING SYARIAH SEBAGAI ALTERNATIF PENDANAAN INVESTASI UNTUK PEMBERDAYAAN UMKM - Salsabilla, Syahvira; Yazid, Muhammad (AMAL: Jurnal Ekonomi Syariah, 2024)
The penetration of information technology in the Industrial Revolution 4.0 era has transformed various aspects of people's lives, including the tradition of giving alms. The LBS crowdfunding platform is present as an innovation of the Sharia Securities Crowdfunding platform that allows people to contribute to community empowerment projects through digital fundraising. This study aims to analyze the potential and challenges of LBS Crowdfunding in encouraging the growth of the sharia economy in Indonesia. This study is a qualitative study with an exploratory descriptive approach. The results of the study indicate that LBS Crowdfunding has great potential in accommodating the funding needs of sharia MSMEs and encouraging financial inclusion. However, there are several challenges that need to be overcome, such as limited regulations, lack of public awareness, and relatively high investment risks. This study suggests increasing sharia financial literacy, developing technological infrastructure, and improving regulations to support the sustainability of LBS Crowdfunding.